Correlation of Inpatient Experience Survey Items and Domains With Overall Hospital Rating. (November 2015) - Kemp, Kyle; McCormack, Brandi; Chan, Nancy; Santana, Maria J; Quan, Hude
Objective: To determine which individual patient experience questions and domains were most correlated with overall inpatient hospital experience. Methods: Within 42 days of discharge, 27 639 patients completed a telephone survey based upon the Hospital-Consumer Assessment of Healthcare Systems and Processes instrument. Patients rated their overall experience on a scale of 0 (worst care) to 10 (best care). Correlation coefficients were calculated to assess the relationships between individual survey questions and domains with overall experience. Results: Questions on provider coordination and nursing care were most correlated with overall experience. Hospital cleanliness, quietness, and discharge information questions showed poor correlation. Correlation with overall experience was strongest for the "communication with nurses" domain. Conclusions: Our individual question results are novel, while the domain-based findings replicate those of US-based providers, results which had not yet been reported in the Canadian context—one with universal health care coverage. Our results suggest that our large health care organization may attain initial inpatient experience improvements by focusing upon personnel-based initiatives, rather than physical attributes of our hospitals.